Ventromedial Preoptic Prostaglandin E2 Activates Fever-Producing Autonomic Pathways - Scammell, Thomas E. (J Neurosci, 1996)
Fever is thought to be initiated by pyrogenic cytokines inducing the production of prostaglandin E2 (PGE2) in the preoptic area (POA); PGE2 may act as a paracrine mediator that stimulates the neural pathways that raise body temperature. This essential role for prostaglandins in fever first was proposed 25 years ago, but the specific preoptic cell groups at which PGE2 acts and the pathways through which fever is produced remain poorly understood. To better define the role of preoptic PGE2 in fever, we developed a new method for combining acute brain injections with Fos immunohistochemistry. We microinjected a threshold dose of PGE2 to construct an anatomically detailed map of fever-producing preoptic sites. The most pyrogenic preoptic sites were clustered along the ventromedial aspect of the POA, surrounding and just anterior to the organum vasculosum of the lamina terminalis. We then used Fos immunohistochemistry to identify the pattern of neural activation induced by fever-producing preoptic injections of PGE2 and compared it with the Fos pattern seen after systemic immune stimulation. PGE2 fever was accompanied by Fos induction in the ventromedial POA and the parvicellular subnuclei of the paraventricular nucleus of the hypothalamus (PVH). In contrast to the Fos pattern seen after intravenous lipopolysaccharide administration, PGE2 injection did not induce Fos in the circumventricular organs or the magnocellular subnuclei of the PVH. These observations establish a potential site of PGE2 action during fever and help define candidate pathways through which fever occurs.